Dampak Perjodohan Terhadap Anak di Desa Rappolemba Kabupaten Gowa - Rismawati K.; Mubarak Dahlan (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2023)
This research aims to discuss arranged marriages in Rappolemba Village. This type of research method is case study research with a qualitative research approach. The informants in this research are those who can answer the research questions. This research uses data collection techniques by conducting observations, interviews and documentation which are then analyzed through three stages, namely, data reduction, data presentation and drawing conclusions. The results of the research show that 1) the process of child matchmaking in Rappolemba Village, Gowa Regency, namely: (a) A'kuta'kuta'nang process (b) Mange Assuro process (c) Panai' Balanja process, (d) Accidong-cidong process, and (d) A'borong-borong process/Wedding reception party. The results of further research are about 2) factors that influence so many parents still match their children in Rappolemba Village, Gowa Regency, namely (a) economic factors, (b) debt factors, and (c) kinship factors. Furthermore, regarding 3) The impact on children caused by arranged marriages in Rappolemba Village, Gowa Regency, namely: Education is disrupted by arranged marriages, after marriage a series of problems arise which are based on various problems, even family quarrels arise which lead to divorce.